Variations of Tentorial Notch Anatomy in Autopsy and NCCT of Head Injury Patients to Correlate Its Impact over Brainstem—An Observational Study - Singh, Anoop Kumar; Ojha, Bal Krishna; Jaiswal, Manish; Bajaj, Ankur; Yadav, Awdhesh (Indian Journal of Neurotrauma, 2024)
Tentorium cerebelli divide cranial cavity into supratentorial and infratentorial compartment. Tentorial notch is a gap in tentorium cerebelli located centrally and anteriorly, related to upper brainstem, first six cranial nerves, cerebrum, and cerebellum. The aim of this study was to analyze morphometric variation in tentorial notch anatomy in autopsy and computed tomography (CT) of head injury patients and to find out correlation between tentorial notch anatomy and uncal herniation and changes over brainstem surface in case of uncal herniation.Autopsy examination of head injury patients was done between July 1, 2021, and Jan 31, 2023. Skull was opened in a standard manner and midbrain sectioned at the level of tentorial edge. Tentorial notch parameters (anterior notch width, maximum notch width, notch length, posterior tentorial length, apicotectal distance, interpedunculoclival distance) were measured using geometry compass and vernier caliper. These parameters were also measured on noncontrast computed tomography (NCCT) head of same patients. Evidence of uncal herniation was sought for in both NCCT head and autopsy examination. Impact of uncal herniation over brainstem in form of indentation over lateral surface of midbrain and macroscopic brainstem hemorrhage was noted.In 65 autopsy cases, there were 56 male and 9 female specimens; their mean age was 40.63 ± 16.78 years (range: 7–86 years). The most frequent type of tentorial notch observed in our study was typical type (32.30%). Relative frequency of uncal herniation was present predominantly (75%) in large type of tentorial notch and least (20%) in small type of tentorial notch. A significant correlation (p-value < 0.01) was found between uncal herniation and indentation over lateral surface of midbrain, while no significant correlation (p-value > 0.05) was found between uncal herniation and macroscopic brainstem hemorrhage in autopsy specimens.The results of our study provide a baseline data about tentorial notch anatomy and it may facilitate neurosurgical decision making as well as help in deciding the best trajectory for lesions approaching in the vicinity of the tentorial notch
Keywords: neuroimaging; postmortem examination; tentorial notch classification; traumatic brain injury; uncal herniation